FYP-SV finder / Muhammad Zaki M A Rasul - M A Rasul, Muhammad Zaki (2017)
People use web based system every, it gives advantages to people who want to search for information regarding anything related to what they want, for instance search for hotel, booking book and also purchases item. Malaysian Communication and Multimedia Commission (MSMS) statistic shows that the number of people using web based system and internet is growth form year to year. As for students, especially student in the final year, they will have to submit a report of a project that they have to make from their own work. In UiTM, every student must find a supervisor for the final year project. However, some problem occurred in UiTM especially in FSKM, where student unable to find a suitable supervisor and does not know the availability of supervisor. Student also unable to identify the criteria of the supervisor that is needed for their final year project. Since, in FSKM we still using the manual way that is student must meet the supervisor face to face in order to know the supervisor and also to request as a supervisee. Therefore, this project is about the study of developing a FYP-SV Finder for Degree in IT department of FSKM. The objective is to determine the supervisor criteria for student in Bachelor of Information Technology, design and develop FYP-SV Finder. With this system, it provides student with a system that tell the availability of the supervisor and determine which supervisor is suitable for them. It also helps student by giving the information of the requirement and the criteria of the supervisor to help them decide which project they wanted to do. The system will give the student the information of the supervisor and the project title. This website also help the supervisor to manage a controllable number of student and also help the supervisor to evaluate the student based on the given criteria and the requirement given. The methodology that is suitable for this project is Web Development life cycle (WDLC). In analysis and findings, the function and non-function requirement, the design and development phase were defined. As conclusion, future work of FSRS can be enhanced by create a match engine where student can match their criteria with the supervisor criteria.